2011
DOI: 10.1007/s10762-011-9797-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Sintering of Silica Xerogel Ceramic Derived from Sago Waste Ash Using Sub-millimeter Wave Heating with a 300 GHz CW Gyrotron

Abstract: In this paper, we present and discuss experimental results from a microwave sintering of a silica-glass ceramic, produced from a silica xerogel extracted from a sago waste ash. As a radiation source for the microwave heating a sub-millimeter wave gyrotron (Gyrotron FU CW I) with an output frequency of 300 GHz has been used. The powders of silica xerogel have been dry pressed and then sintered at temperatures ranging from 300°C to 1500°C. The influence of the sintering temperature on the technological propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…The detailed extraction procedures are described elsewhere (Affandi et al, 2009;Aripin et al, 2011;. High-purity amorphous silica amounting to 98.8% has been observed (Aripin et al, 2011).…”
Section: Silica Xerogel and Tio 2 Composite Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed extraction procedures are described elsewhere (Affandi et al, 2009;Aripin et al, 2011;. High-purity amorphous silica amounting to 98.8% has been observed (Aripin et al, 2011).…”
Section: Silica Xerogel and Tio 2 Composite Preparationmentioning
confidence: 99%
“…Therefore, SiO 2 production from these sources on an industrial scale is not technologically or economically viable. In our study, SiO 2 in the form of silica xerogel was prepared using a sago waste ash (Aripin et al, 2011;Aripin et al, 2012) as a starting powder and was used to produce TiO 2 -SiO 2 composites by mixing 20 wt% and 40 wt% of TiO 2 into SiO 2 . It was found that, at 900°C, the size of the anatase crystallites are 26.3 nm and 21.4 nm for 20 wt% and 40 wt% of TiO 2 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The same requirement is imposed also by many other technologies that utilize gyrotrons as sources of powerful sub-THz and THz waves, for example, materials treatment (e.g. sintering of advanced ceramics, development of new functional materials) [23]- [25], biological and medical applications [26]- [28], just to name a few. Additional features demanded by some of the above-mentioned applications are frequency and amplitude modulation and stabilization, as well as frequency tunability.…”
Section: Introductionmentioning
confidence: 99%
“…For sintering of various materials such as ceramic, metal matrix composites and metal powder compacts, there is lots of interest nowadays to use the microwave energy as it offers several advantages such as the volumetric and selective heating, improved product quality, energy savings, self cooling system, better precision in controlling the process of energy deposition, and reduction in manufacturing costs, over the conventional heating methods [1,2]. In recent years, the iron powders are widely investigated for their applicability in many fields such as for various strategic applications, magnetic applications, in electronic industry as RF transformers, EMI filters, switch mode power supplies, and absorbent fillers.…”
Section: Introductionmentioning
confidence: 99%